ANALISIS PRAGMATIS SERAT SOTIYARINONCE KARYA RADEN SOERJAPRANATA - , BANU BADRIKA, Drs. Akhmad Nugroho, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Serat Sotiyarinonce (1911), Raden Soerjapranataâs work, is manuscript collection of Perpustakaan Kirti Griya, Perguruan Taman Siswa, Yogyakarta. The manuscript is about didactic lessons (education) in prose version. Based on the content, the manuscript can be grouped in Sastra Wulang, which is the literature contains lessons for the readers. The lessons theme is about a personal character building, social life, work, married, children educating, health, and gambSling and opium forbidding. The literature is made for graduate student of school. The expectation is the graduate student will be ready for life in society, doing the real practice, no more theory. The research provides text editing and translation from Javanese into Indonesian simply, and then it analyzes the literature with pragmatic criticism. In brief, pragmatic analysis is the way to analyze a literature from the readerâs point of view. It is important because the reader is the literature interpreter and the main indicator that determines the literature quality. Reading is not a simple matter. The author and the reader have difference knowledge and thought. Perhaps it is may also represent their own era. The author of Serat Sotiyarinonce in Batavia 1911 and the reader of 2013 have 102 years stretch of time. It is clear that author and reader have many different concept and thought. The word âperangâ in 1911 may be considered as a gallance and nationalistic action. It is different with âperangâ concept in 2013, which has violent and barbaric value. These are the differences that research wants to analyzes.